Teaching medical students hematopathology: a randomized crossover study comparing direct inspection by light microscope versus projected images - Alqahtani, Sultan; Al-Nasser, Sami; Agha, Sajida; Mohamud, Mohamud S. (Frontiers in Medicine, 2024)
Background: Students' ability to diagnose various blood disorders could be substantially improved by continuously reviewing approaches toward teaching hematology. This study aims to compare the effectiveness of light microscopes and projected images on students' learning and determine medical students' perception of these teaching methods. Methods: A randomized trial was conducted using a crossover design. Two groups, each with 30 students, were subjected to teaching methods based on light microscopes and projected images alternatively. Results: No differences were found in the two study groups' baseline characteristics, such as median age, sex, and prior academic performance, as well as in the pre-test scores. Post-test scores were significantly higher among students subjected to the projection method than in the control group (Mean+SD= 9.8+1.7 vs. 5.1+1.3, p<0.001). In the post-cross-over assessment, 85% (n = 51) of students reported their satisfaction for the projected images, and 78% (n = 47) of students were willing to be taught by projection. Students perceived that the projection method facilitated participation and better involvement in discussions, improved learning, provided greater motivation, and eventually increased comprehension and efficiency. The projection-based teaching method is more effective in improving knowledge and achieving intended learning outcomes. Students tend to prefer the projection method over the laboratory-based method and perceive it as an effective method to enhance their learning of hematology.